Effect Of Laparoscopic Tubal Disconnection For The Management Of Hydrosalpinx Before ICSI On Ultrasonographic Markers Of Endometrial Receptivity, Ovarian Blood Flow And Volume (Journal of Pharmaceutical Negative Results, 2023)
Objective The aim of this study was to investigate the effect of laparoscopic tubal disconnection for the management of hydrosalpinx before ICSI on ultrasonographic markers of endometrial receptivity, ovarian blood flow and volume. Methods Infertility treatment candidate women were divided into two groups, the hydrosalpinx group (HxG) and the non-hydrosalpinx group, totaling 120 women (nHxG). 60 women in the HxG experienced hydrosalpinx, whereas 60 women in the nHxG had unexplained infertility. LH levels in urine samples were used to identify an LH peak. On cycle day LH+6, the TVUS examination was solely done in the HxG. Laparoscopic tubal disconnection was then carried out. On day LH+6 of the cycle, which came before the ICSI cycle, the same ultrasonographic measurements were then collected in both groups. Outcome measures Uterine a. RI and PI, spiral a. RI and PI, ovarian a. RI and PI, endometrial thickness, pattern and volume, endometrial VI, FI and VFI and ovarian VI, FI, VFI and volume and zone of vascular penetration. Results We found no measurably massive contrasts between the two gatherings in the uterine a. RI and PI, winding a. RI and PI, ovarian a. RI and PI, endometrial thickness and volume (p=0.642), or the nHxG following tubal separation.endometrial VI (p=0.887), FI (p=0.646) and VFI (p=0.652) and ovarian VI (p=0.648), FI (p=0.646) , VFI (p=0.638) and ovarian volume (p=0.646), endometrial example and zone of vascular infiltration. Conclusions Laparoscopic tubal disconnection has no significant effect on endometrial, subendometrial, uterine, ovarian blood flow, endometrial and ovarian volumes, endometrial pattern and zone of vascular penetration.